Sociocultural integration of bilingualism and biliteracy of emiratis: exploratory study in a group of fifth-grade students - Alshamsi, Aysha; Alsheikh, Negmeldin Omer (Penerbit Universiti Kebangsaan Malaysia, 2020)
This study explores the sociocultural integration of bilingualism and biliteracy practices of a group of Emirati fifth-grade students, who were learning English and Arabic and using English as the medium of instruction for math and science. The explanatory, mixed methodology study examines how sociocultural aspects of language learning are integrated in the learners’ bilingualism and biliteracy practices by using both quantitative and qualitative means. In the first phase, a group of fifth-grade students (n = 350), selected for the transitional nature of their grade cycle, and their Arabic and English teachers (n = 350) were surveyed on their bilingualism and biliteracy practices, with a particular focus on sociocultural factors. The second qualitative phase featured a more in-depth investigation of these practices through interviews with two English teachers, two Arabic teachers, and three students. The results revealed that the fifth-grade students did not possess adequate bilingualism and biliteracy abilities in English or, to a lesser degree, in Arabic, for their expected grade level. The reasons included lack of continuous bilingual/biliteracy interactions, lack of parental involvement and absence of a rich school context. Further, there have been no orchestrated efforts to engage the students with the sociocultural aspect of language learning. Thus, integrating the multifaceted aspects of bilingualism and biliteracy contexts and practices is strongly recommended in order to enrich these linguistic approaches to enable fifth graders excel in both languages, and to improve cross-linguistic transfer.